Pertumbuhan Secara In VitroTunas Buah Naga Merah (Hylocereus polyrhizus [Weber] Britton & Rose) Dengan Penambahan Naftalene Acetic Acid (NAA) Dan Air Kelapa - Mukarlina, Berta Rendani Riza Linda, (Universitas Tanjungpura, 2015)
The growth of purple pitaya shoot in tissue culture is influenced by many factors, among others, the composition of growth media and growth regulators used. This research aimed to find out the effect of adding coconut water and Naftalene Acetic Acid (NAA) as well as the best concentration for the growth of purple pitaya (H. polyrhizus). This research was carried out for 5 months from March to August 2015 at the Laboratory of Tissue Culture of the Aloe Vera Center (AVC), Regional Technical Implementation Unit (UPTD) of Agribusiness Pontianak. This rsearch used a completely randomized factorial design (CRD) with 2 factors of treatment. The first factor of NAA at concentrations of (N0), 10-6M (N1), 5X10-7M (N2), 10-7M (N3), and the second factor of coconut water at concentrations of 0% (K0), 10% (K1), 15% (K2), and 20% (K3). The research findings indicated that the single addition of coconut water at a concentration of 20% encouraged the fastest appearance of shoots, i.e. 19.25 days, the highest number of shoots with an average of 6.83 shoots and the longest shoots with an average of 3.30 cm.